2009
DOI: 10.17953/appc.7.1.76h786l18u77l541
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of K–12 Filipina/o American Curriculum

Abstract: This research study provides the first comprehensive and critical literature review of K-12 Filipina/o American curricula found in formal and informal educational settings. Thirty-three Filipina/ o American curricula representing a diverse array of authors, audiences, content, and pedagogical approaches were reviewed. The authors of this study developed a "Critical Framework of Review" rooted in critical pedagogy in order to analyze the historical development of Filipina/o American curricula along with an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…Consistent with previous research, participants began to claim a Filipino identity after experiences in higher education (Buenavista, Jayakumar, and Misa-Escalante 2009; Halagao et al 2009; Nadal 2004; Strobel 1996, 2001; Tuason et al 2006). While Melanie attended college in the continental United States, she fell in love with Asian American studies because it was the first place that she found “that community—young people expressing themselves and finding Filipino American [through] poetry, dance, or hip-hop.” In her second year, she transferred home to a community college in Hawai’i and found a Filipino American studies program.…”
Section: Being a Role Model And Pushed Into Filipinosupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with previous research, participants began to claim a Filipino identity after experiences in higher education (Buenavista, Jayakumar, and Misa-Escalante 2009; Halagao et al 2009; Nadal 2004; Strobel 1996, 2001; Tuason et al 2006). While Melanie attended college in the continental United States, she fell in love with Asian American studies because it was the first place that she found “that community—young people expressing themselves and finding Filipino American [through] poetry, dance, or hip-hop.” In her second year, she transferred home to a community college in Hawai’i and found a Filipino American studies program.…”
Section: Being a Role Model And Pushed Into Filipinosupporting
confidence: 77%
“…Scholars argue that these educational experiences are crucial to the process of decolonizing the mind (David 2011; David and Okazaki 2006a; Freire 1970; hooks 2010; Nadal 2004; Strobel 1996; Tuason et al, 2006) because they provide an opportunity to question the ideology of “cultural inferiority based on master narratives that portray Filipinos as either having a damaged culture or none at all” (Strobel 1996:40). It is vital that these educational spaces enable students to reflect on Filipino identity rather than merely replace a negative narrative with a positive one (Halagao, Tintiangco-Cubales, and Cordova 2009). Daniel B. Eisen et al (2015) show that although positive conceptualizations of Filipino culture can combat an individual’s shame in being Filipino if the conceptualizations are rooted in essentialist depictions, they can continue to divide communities and prevent critical explorations of Filipino identity.…”
Section: Filipino Identity Developmentmentioning
confidence: 99%
“…Our analysis suggests that much of the research in this area was created by scholars responding to the dismal lack of culturally responsive pedagogies in the first place. Key scholars developed a curricular framework of review that is grounded in critical pedagogy and has application to other minoritized groups (Halagao et al, 2009;Tintiangco-Cubales et al, 2020). Scholars whose research we analyzed under the broader theme of cultural relevance simultaneously produced educational interventions resulting in curricula, pedagogies, and programs that support the academic, social, cultural, and political identities of their participants (Halagao, 2004;Tintiangco-Cubales & Sacramento, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars also anchored their focus on Filipinx Americans in education through Ethnic Studies to develop tools applicable to fields including curriculum studies and teacher preparation (Curammeng et al, 2016;Halagao et al, 2009;Tintiangco-Cubales & Sacramento, 2009). Tintiangco-Cubales et al's (2010) study on Pin@y Educational Partnerships (PEP) serves as a transformative intervention for the development of Filipino American studies, Filipino American curricula, and research.…”
Section: Critical Pedagogy and Ethnic Studiesmentioning
confidence: 99%
“…Approximately 400,000 Filipino Americans are currently enrolled in higher education, while the Filipino American ethnic group is the second largest within the Asian American racial category and also growing at the second fastest rate (U.S. Census Bureau, 2012). Despite these significant demographic growths, the needs and capabilities of Filipino American students are rendered largely invisible within higher education discourse and education policy in general (Halagao et al., 2009; Maramba and Bonus, 2013). This omission is due not only to the homogenization of over 40 different ethnic groups under the aggregate category of Asian Americans but also the incongruence of Filipino Americans with stereotypes that categorize Asian Americans, both writ large and within an educational environment, as overachieving foreigners and passive, apolitical subjects (Wu, 2002).…”
mentioning
confidence: 99%